2014
DOI: 10.1002/mnfr.201400293
|View full text |Cite
|
Sign up to set email alerts
|

Carnosic acid suppresses colon tumor formation in association with antiadipogenic activity

Abstract: CA appears to alleviate adipocity-related acceleration of colon tumor formation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(19 citation statements)
references
References 46 publications
1
18
0
Order By: Relevance
“…Correspondingly, the number of colon tumors in mice nurtured with HFD supplemented with carnosic acid reduced to 6.7-8.4 in comparison to 12.7 tumors in HFD mice [33]. This study thus highlights the anti-adipogenic activity of carnosic acid in addition to its anti-carcinogenic activity.…”
Section: In Vivo Studiesmentioning
confidence: 68%
See 1 more Smart Citation
“…Correspondingly, the number of colon tumors in mice nurtured with HFD supplemented with carnosic acid reduced to 6.7-8.4 in comparison to 12.7 tumors in HFD mice [33]. This study thus highlights the anti-adipogenic activity of carnosic acid in addition to its anti-carcinogenic activity.…”
Section: In Vivo Studiesmentioning
confidence: 68%
“…Metabolomics study showed increase in reduced intracellular GSH levels in treated HT-29 cells further demonstrating the chemopreventive response of these cells to carnosic acid treatment[31]. In a different study 1µM and 10µM of carnosic acid inhibited growth of HT-29 cells by exhibiting significant accumulation of cells in the S phase with decreased expression of cyclinD1 and CDK4 along with apoptosis induction[33]. Interestingly, this study highlights the use of carnosic acid in alleviating adiposity related acceleration of colon cancer formation.…”
mentioning
confidence: 87%
“…Of note, levels of GSH, an important antioxidant, were enhanced and levels of N -acetylputrescine, which are toxic in high doses, were decreased [51]. In HT-29 cells co-cultured with 3T3-L1 adipocytes, CA attenuated the negative effects of the adipocytes on the colon cancer cells by inhibiting triglyceride accumulation and downregulating expression of the Ob-R receptor [52]. In these cells CA also inhibited cell viability by decreasing phosphorylation of the cell survival regulators Akt and Bcl-xL and enhancing Bax expression.…”
Section: Anticancer Effects Of Carnosic Acid (Ca): In Vitro Studiesmentioning
confidence: 99%
“…In these cells CA also inhibited cell viability by decreasing phosphorylation of the cell survival regulators Akt and Bcl-xL and enhancing Bax expression. Furthermore, cell cycle arrest was induced by inhibition of cyclin D1 and CDK4 [52]. Similarly, a fraction of rosemary extract which was found to consist mainly of CA (98.7% pure) was tested on HT-29, SW480 and HGUE-C-1 colon cancer cells and significantly inhibited cell viability.…”
Section: Anticancer Effects Of Carnosic Acid (Ca): In Vitro Studiesmentioning
confidence: 99%
“…Cellular mechanisms involved in the effects of carnosic acid include up-regulation of Nuclear factor (erythroid-derived 2)-like 2 (Nfr2) activity [8, 13,55,56], preservation of mitochondrial respiratory function [11,56], mitochondrial depolarization [47], cytochrome-c release [36], increase in Bax:Bcl-2 ratio [36], caspase activation [36,37], up-regulation of NAD + -dependent deacetylase SIRT1 [2], glutathione S-transferase [8,57], death receptor (DR)5 [19], Bcl-2 interacting mediator of cell death (Bim) [19] and p53 up-regulated modulator of apoptosis (PUMA) [19] expression, down-regulation of c-FLIP and Bcl-2 expression [19] as well as stimulation of PGE 2 synthesis [15]. Signaling involved in the effect of carnosic acid further includes phosphatidylinositol 3-kinase (PI3K)/Akt [26,[46][47][48][49], nuclear factor-kappa B (NF-κB) [21,49], and p38 kinase [8, 16,45,57].…”
Section: Introductionmentioning
confidence: 99%